Impact of type 1 diabetes and its duration on wall-to-lumen ratio and blood flow in retinal arterioles - Stefański, Adrian; Wolf, Jacek; Harazny, Joanna M.; Miszkowska-Nagórna, Eliza; Wolnik, Bogumił; Murawska, Joanna; Narkiewicz, Krzysztof; Schmieder, Roland (Microvascular Research, 2023)
Background: Subclinical damage to both the small and large vessels may contribute to the development and progression of cardiovascular disease. Scanning laser Doppler flowmetry (SLDF), an established method used to measure retinal microcirculation, has been successfully applied in hypertensive and post-stroke patients. Methods: Retinal microcirculation was assessed in 158 patients with type 1 diabetes and 38 age-matched healthy controls. The diabetics were divided into 3 groups: group A with diabetes duration <12 months, group B with diabetes with 1–10 years, and group C >10 years of diabetes. Retinal capillary structure and perfusion were evaluated using a Heidelberg retina flowmeter and automatically analyzed with full-field perfusion imaging. Results: Age and BMI were comparable in all the diabetic patients and the controls (mean age 24.8 ± 4.7 years, mean BMI 22.9 ± 4.1). In the univariate analyses, RCF (retinal capillary flow) was significantly higher in group A (297 ± 121 arbitrary units [AU]) vs group B (236 ± 52 AU; p = 0.007) and group C (236 ± 70 AU; p = 0.008) and comparable to that of the controls (p = 0.46). Additionally, the WLR (Wall-to-Lumen Ratio) was highest in group C compared to the other diabetic subgroups and controls (p = 0.001). Multivariate regression analyses including age, BMI, sex, HbA1c, smoking, systolic blood pressure, and diabetes duration as covariates, showed, that only diabetes duration was significantly associated with WLR variations, whereas HbA1c was significantly linked to retinal capillary flow levels. Conclusions: New-onset diabetes is associated with an increase in RCF, which then gradually decreased with the duration of the disease. Structural changes of the retinal arterioles estimated via WLR are evident later in the course of diabetes, especially when the disease duration exceeded 10 years.
CRIS-Team Scopus Importer:2023-02-17
Keywords: Arterioles remodeling; Cardiovascular disease; Retinal microcirculation; Scanning laser Doppler Flowmetry; SLDF; Subclinical organ damage; Type 1 diabetes; Wall-to-lumen ratio